2022
DOI: 10.1002/cjoc.202200302
|View full text |Cite
|
Sign up to set email alerts
|

What Defines a Crystal Structure? Effects of Chalcogen Atoms in 3,7‐Bis(methylchalcogeno)benzo[1,2‐b:4,5‐b′]dichalcogenophene‐Based Organic Semiconductors

Abstract: To understand the effects of chalcogen atoms on the crystal structure of the series of 3,7-bis(methylchalcogeno)benzo[1,2-b:4,5-b′+dichalcogenophene-based organic semiconductors, three benzodifuran derivatives (1-3) and dimethoxy derivatives of benzodithiophene and benzodiselenophene (4 and 7) were newly synthesized to complete the "3 × 3 matrix" of the oxygen-, sulfur-, and selenium-derivatives (1-9). The crystal structures of 1-9 were classified into four classes, sandwich pitched -stack (1), dimeric (2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“… a Calculated on the basis of the crystal structures measured at 300 K. b From ref . c From ref . d See the Supporting Information. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… a Calculated on the basis of the crystal structures measured at 300 K. b From ref . c From ref . d See the Supporting Information. …”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, we coincidentally observed that β-methylthiolated benzo[1,2-b:4,5-b′]dithiophene (β-MT-BDT, Figure 1) crystallized into a pitched π-stacking structure in 2017. 15 This discovery was followed by the synthesis of a series of β-MT-BDT-related molecules, e.g., its oxygen and selenium analogues (β-MX-BDX, Figure 1) 16,17 and π-extended derivatives, 18 and their crystal structures were elucidated by single-crystal X-ray analysis. We found that β-methylchalcogenolation is a reliable and general molecular design strategy for realizing acenedichalcogenophene derivatives with pitched πstacking structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Se⋯N chalcogen bond formation, an effect which is magnified in the molecular packing by the observation that Se⋯N chalcogen bonds increase the aromaticity of rings within their molecules which then enhances their likelihood of forming π⋯π interactions with consequent impact upon charge transport and magnetic properties. 102,165,166…”
Section: An Evaluation Of Congeners Of 1–88 For the Presence Of Relat...mentioning
confidence: 99%
“…Se⋯N chalcogen bond formation, an effect which is magnified in the molecular packing by the observation that Se⋯N chalcogen bonds increase the aromaticity of rings within their molecules which then enhances their likelihood of forming π⋯π interactions with consequent impact upon charge transport and magnetic properties. 102,165,166 The attention now turns to seeking correlations between the Ch⋯N separation and/or Y-Ch⋯N with Ch = Se on the one hand, and Ch = Te or S on the other. Geometric data in support of this analysis are presented in Table 8.…”
Section: An Evaluation Of Congeners Of 1-88 For the Presence Of Relat...mentioning
confidence: 99%
“…9 In recent years, there have been comparative studies of sulfur and selenium atoms, which are located in the same main family, with the former being of almost continuous interest. [27][28][29] Because selenium's position in the periodic table of elements indicates that it has a greater mass and volume than sulfur, then whether the introduction of selenium atoms would bring about a more outstanding performance in terms of changing the molecular stacking and maintaining the stability of the devices made of its molecules in practical applications is not clear. Recently, anti-b-MS-BDT was synthesized experimentally, and it was reported to have the characteristics of 2D brickwork p-stacking, 30 which would be conducive to charge transport.…”
Section: Introductionmentioning
confidence: 99%